A New Pathway for Protein Haptenation by β‐Lactams. Issue 56 (12th September 2017) - Pérez‐Ruíz, Raúl; Lence, Emilio; Andreu, Inmaculada; Limones‐Herrero, Daniel; González‐Bello, Concepción; Miranda, Miguel A.; Jiménez, M. Consuelo
Abstract: The covalent binding of β‐lactams to proteins upon photochemical activation has been demonstrated by using an integrated approach that combines photochemical, proteomic and computational studies, selecting human serum albumin (HSA) as a target protein and ezetimibe (1 ) as a probe. The results have revealed a novel protein haptenation pathway for this family of drugs that is an alternative to the known nucleophilic ring opening of β‐lactams by the free amino group of lysine residues. Thus, photochemical ring splitting of the β‐lactam ring, following a formal retro‐Staudinger reaction, gives a highly reactive ketene intermediate that is trapped by the neighbouring lysine residues, leading to an amide adduct. For the investigated 1 /HSA system, covalent modification of residues Lys414 and Lys525, which are located in sub‐domains IIIA and IIIB, respectively, occurs. The observed photobinding may constitute the key step in the sequence of events leading to photoallergy. Docking and molecular dynamics simulation studies provide an insight into the molecular basis of the selectivity of 1 for these HSA sub‐domains and the covalent modification mechanism. Computational studies also reveal positive cooperative binding of sub‐domain IIIB that explains the experimentally observed modification of Lys414, which is located in a barely accessible pocket (sub‐domain IIIA). Abstract : Cause of photoallergy : A new haptenation mechanism of β‐lactams drugs, which constitute the key step in the sequence of events leading to photoallergy, has been identified. Selecting human serum albumin as a target protein and ezetimibe as a probe, the covalent modification of Lys414 and Lys525 residues (located in sub‐domains IIIA and IIIB) has been identified (see figure).